2022
DOI: 10.1097/md.0000000000028601
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of physical exercise programs toward people with acquired brain injury

Abstract: Background: Exercise has proven to be a tool improving health related quality of life in people with acquired brain injury (ABI) as part of multidisciplinary team during the subacute and chronic phase. While intervention studies and revisions have been increased in recent years, there is no consensus about the type, frequency and variables of control in exercise interventions. Besides, this collective need programs that respond to different functional levels, given the heterogeneity of people with ABI, not onl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“…21,25,26,27 More studies integrating tools such as sport are needed to achieve higher levels of social inclusion in their therapeutic approach. 14,29,30,59 The current designed program provides a more holistic approach that combines exercise therapy and sport-based functional tasks that can be easily integrated into participants' daily life activities. If this program is found to be effective, multidisciplinary teams will have an evidence-based mode of therapy to offer, i.e.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…21,25,26,27 More studies integrating tools such as sport are needed to achieve higher levels of social inclusion in their therapeutic approach. 14,29,30,59 The current designed program provides a more holistic approach that combines exercise therapy and sport-based functional tasks that can be easily integrated into participants' daily life activities. If this program is found to be effective, multidisciplinary teams will have an evidence-based mode of therapy to offer, i.e.…”
Section: Discussionmentioning
confidence: 99%
“…9,10,11,12 Some systematic reviews point to the effectiveness of exercise therapy intervention programs, and favourable results of physical activity programs in people with ABI, leading to activation of supplementary motor areas, and augment more consistent motor recovery than only standard care. 13,14,15,16,17 Multidisciplinary approaches oriented to exercise therapy and social leisure activities seem to be fundamental to elicit neuroplastic adaptations to enhance physical recovery, 16,18,19,20 and to improve the cognitive and behavioural sequels after ABI. 21,22 Considering the principles of motor learning, the dynamic interaction between systems including the demanding task of a real sport, allowing neuro-plastic adaptations and underlying behavioural improvement for the patients and achieving a motivating functional context.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, based on the long-term or lifelong injury related sequelae that can extend for 10–20 years after moderate-to-severe TBI, PA is particularly relevant as a self-management tool in the chronic period of recovery ( 5 ), as it has been shown that adults with moderate-to-severe TBI can, with minimal guidance, perform vigorous community-based PA ( 6 ). Although best-practices for maintaining community-based PA after moderate-to-severe TBI have yet to be defined ( 7 , 8 ), participatory approaches to developing PA programs (e.g., partnering with stakeholders) are more successful because they are tailored to the unique needs and resources of the target community ( 9 ). Participatory approaches to developing health-related programs after TBI can also lead to additional outcomes based on the collaboration itself, such as increased cultural competency (appropriate communication with people of other cultures), community capacity (social capital), and ownership of the program ( 10 ).…”
Section: Introductionmentioning
confidence: 99%
“…Acquired brain injury (ABI) is an overarching term to describe damage to the brain occurring from traumatic or non-traumatic causes; it is considered a public health condition often resulting in deficits of physical, cognitive, and emotional functions (Calabro et al, 2018;Perez-Rodriguez et al, 2022). ABI can be caused by strokes, infections, toxins, tumors, or accidents (Calabro et al, 2018;Materne et al, 2018).…”
Section: Acquired Brain Injurymentioning
confidence: 99%